2017
DOI: 10.1146/annurev-neuro-072116-031418
|View full text |Cite
|
Sign up to set email alerts
|

Circuits and Mechanisms for Surround Modulation in Visual Cortex

Abstract: Surround modulation (SM) is a fundamental property of sensory neurons in many species and sensory modalities. SM is the ability of stimuli in the surround of a neuron’s receptive field (RF) to modulate (typically suppress) the neuron’s response to stimuli simultaneously presented inside the RF, a property thought to underlie optimal coding of sensory information and important perceptual functions. Understanding the circuit and mechanisms for SM can reveal fundamental principles of computations in sensory corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
286
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(333 citation statements)
references
References 176 publications
16
286
5
1
Order By: Relevance
“…Layer 2/3 suppression peaked at times quite delayed compared to facilitation. Both the orientation selectivity and delayed emergence of this tuned suppression are consistent with it arising as a result of cortico-cortical lateral interactions, as often postulated before (reviewed in Angelucci et al, 2017). We found that this suppressive component arises from extended spatial scales, with most of it generated by the activity of V1 neurons with receptive fields more than 2 x CRF radius away from the recorded neuron.…”
Section: Mechanisms Of Ecrf Modulation and Link To V1 Laminar Circuitssupporting
confidence: 90%
See 2 more Smart Citations
“…Layer 2/3 suppression peaked at times quite delayed compared to facilitation. Both the orientation selectivity and delayed emergence of this tuned suppression are consistent with it arising as a result of cortico-cortical lateral interactions, as often postulated before (reviewed in Angelucci et al, 2017). We found that this suppressive component arises from extended spatial scales, with most of it generated by the activity of V1 neurons with receptive fields more than 2 x CRF radius away from the recorded neuron.…”
Section: Mechanisms Of Ecrf Modulation and Link To V1 Laminar Circuitssupporting
confidence: 90%
“…Long-distance V1 lateral connections must be in some way selective for the orientation of their targets in order to support such long-range tuned suppression. If instead this suppression is caused in part by extra-striate feedback (Angelucci et al, 2002(Angelucci et al, , 2017Nassi et al, 2013), then those feedback circuits must also be matched in orientation selectivity to their V1 targets. Tuned suppression is also present in layer 4B but it differs quantitatively from that of layers 2/3.…”
Section: Mechanisms Of Ecrf Modulation and Link To V1 Laminar Circuitsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess suppressive modulatory mechanisms in humans with ASD, we measured visual spatial suppression, a phenomenon in which larger moving stimuli are more difficult to perceive 28 . This mirrors a well-known neural phenomenon; when stimuli extend beyond a neuron's spatial receptive field, neural responses in visual cortex are suppressed through a combination of feed-forward, lateral, and feedback interactions 18,19,29 . Based on work in both humans 1,30,31 and non-human primates [32][33][34][35] , it is thought that neural surround suppression within the motion-selective visual area MT plays an important role in the perceptual phenomenon of spatial suppression during motion discrimination.…”
Section: Resultssupporting
confidence: 54%
“…This alternative account predicts that weaker suppression in ASD may not be widespread and would manifest only under specific circumstances. For example, in the visual system, suppressive modulatory mechanisms are engaged when a stimulus extends beyond the spatial receptive field of a given neuron 18,19 . Although it has been suggested that suppressive visual surround modulation reflects neural inhibition 20 , work from our group and others has recently called this assumption into question 1,21,22 .…”
Section: Introductionmentioning
confidence: 99%